2019
DOI: 10.3390/ijerph16060998
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Justice in Industrially Contaminated Sites. A Review of Scientific Evidence in the WHO European Region

Abstract: In the WHO European Region the topic of contaminated sites is considered a priority among environment and health themes. Communities living in or close to contaminated sites tend to be characterized by a high prevalence of ethnic minorities and by an unfavorable socioeconomic status so rising issues of environmental justice. A structured review was undertaken to describe the contents of original scientific studies analyzing distributive and procedural justice in industrially contaminated sites carried out in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 91 publications
0
40
0
1
Order By: Relevance
“…This work provides an update to previous work published in 2010 referred to earlier and as such, search results were restricted to articles published between 1 January 2010 and 31 December 2017. Studies were focused on ambient air quality with point source pollution excluded as they form part of another review [21].…”
Section: Methodsmentioning
confidence: 99%
“…This work provides an update to previous work published in 2010 referred to earlier and as such, search results were restricted to articles published between 1 January 2010 and 31 December 2017. Studies were focused on ambient air quality with point source pollution excluded as they form part of another review [21].…”
Section: Methodsmentioning
confidence: 99%
“…The declaration from the WHO Regional Office for Europe Ministerial Conference on Environment and Health, held in 2017 in Ostrava, stated the need to prevent and eliminate the adverse environmental and human health effects, costs and inequalities related to waste management and contaminated sites [66]. Nevertheless, no estimates on the overall health impact or assessment on socioeconomic and sociodemographic inequalities in contaminated sites, such as urban waste landfill or waste treatment plants, was available in Europe at that moment [67][68][69]. A survey carried out by the European Environment Information and Observation Network in 2013 reported that waste disposal and treatment are estimated to contribute to more than 37% of contaminated sites [70].…”
Section: Discussionmentioning
confidence: 99%
“…Ard, 2015;Ash & Boyce, 2018;Banzhaf, Ma, & Timmins, 2019;Crowder & Downey, 2010;Mohai & Saha, 2015) and in Europe (e.g. Diekmann & Meyer, 2010;Glatter-Götz, Mohai, Haas, & Plutzar, 2019;Pasetto, Mattioli, & Marsili, 2019;Rüttenauer, 2018) have documented the unequal distribution of environmental hazards across different social groups.…”
Section: Introductionmentioning
confidence: 99%